Biomasonry products from macroalgae: A design driven approach to developing biomaterials for carbon storage - Kate Scardifield; Nahum McLean; Unnikrishnan Kuzhiumparambil; Peter J. Ralph; Nicolas Neveux; Geoff Isaac; Tim Schork (Journal of Applied Phycology, 2024)
Lowering the embodied carbon of building materials requires a transition away from fossil derived products towards bio-based alternatives, alongside the design and development of new clean tech biomaterials that can function as carbon sinks. This paper presents an overview of historical and existing uses of seaweeds in construction to identify gaps and opportunities for the development of seaweed-based construction materials that can support atmospheric carbon removal through algal photosynthesis. This study highlights the value of interdisciplinary research collaborations that can be situated within the expanding field of biodesign where design research and methods are used to influence the development materials science. It presents as a case study the design of seaweed bricks utilising a biorefinery framework that aims to valorise residual seaweed biomass being grown for waste-water management, identifying value-adding opportunities for this seaweed by-product and new possibilities for carbon storage in the built environment. It details the development of a 1:1 scale prototype for the purposes of an exhibition at the Art Gallery of South Australia in order to demonstrate what biomasonry products from macroalgae can look like, to build social acceptance and to encourage future uptake of sustainable seaweed construction products.